Analysis and synthesis of microwave active filters for present and new generations of mobile communication systems in the 0.8 and 1.7 GHZ band - 203251 Kamaruddin Abdul Ghani (Kuala Lumpur : UTM, 1995)
Various strategies of development of microwave active filter concentrating on smaller sizes, more stable and higher Q filters for Mobile and Personal Communication Systems are disicussed. Among the most popular techniques, active filters based on microstrip resanator attracts many researchers in the development of active filters making use of active elements such as transistors and diodes. basically, passive resonator p[roduced the desired amplitude response and varactor diode connected to it provide the tuning facilities. External active loop coupled to the resonator compensates the losses and ensures the system stability and higher Q performance. Real world modeling and realization of tunable microwave active filters based on coplanar line resonators are presented for operating in Mobile Communication System at the 800 MHz band and in future Personal Communication System at the 1.7 GHz band.